Characterization of lipid oxidation in plant oils by micro-calorimetry. (15th April 2016) - Dridi, Wafa; Toutain, Jean; Sommier, Alain; Essafi, Wafa; Gargouri, Mohamed; Leal-Calderon, Fernando; Cansell, Maud
Highlights: Microcalorimetry allowed monitoring lipid oxidation in real time. Enthalpy values were correlated with primary oxidation products. An oxidability parameter was deduced from the enthalpy measurements. Oxidability was correlated with the n-3 fatty acid content of virgin oils. Abstract: A new experimental device was developed, based on the measurement of the heat flux dissipated during chemical reactions. The technique was exploited for real time monitoring of lipid oxidation in plant oils. The thermopiles were used in adiabatic configuration in order to measure the entire heat flux and improve sensitivity. Measurements were operated with a resolution of few μW as required to follow low exothermic reactions like oxidation. The validation of the device was performed by correlating conjugated diene concentrations measured by spectrophotometry and the heat flux dissipated by oxidation reactions. Our experimental approach involved several plant oils analyzed in isothermal conditions. This novel technique provides a versatile, sensitive, solvent-free and yet low-cost method to assess lipid oxidation stability, particularly suitable for the fast screening of plant oils.